Developing Innovation Capability: Between Individual and Organizational Factors - Nugroho, Yunianto Agung; Putra, Firdaus; Novitasari, Dewiana; Asbari, Masduki; Purwanto, Agus (IJOSMAS, 2020)
The purpose of this study was to measure the influence of individual soft skills as individual factor on lecturer innovation capability through organizational learning as a organizational factor and mediating variable. Data were collected by using simple random sampling to the lecturer population of a private higher education in Indonesia. The number of returned and valid questionnaires was 103 samples. Data were processed by using SEM with SmartPLS 3.0. The results of the study concluded that individual soft skills had positive and significant influence on lecturer innovation capability, both directly and indirectly through a mediating effect of organizational learning. This study proposed a model for improving lecturer innovation capability of lecturers in Indonesia through individual soft skills (as individual factor) and organizational learning (as organizational factor). This study can open the way to improve lecturer readiness in facing education 4.0 era.